Cost effectiveness of bilateral risk-reducing mastectomy and salpingo-oophorectomy - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Csorba, Roland; Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (European Journal of Medical Research, 2019)
BACKGROUND: Growing demand for risk-reducing surgery in individuals with inherited susceptibility to cancer leads to the question whether these procedures are cost effective for the executing hospitals. This study compared the clinical costs for bilateral risk-reducing mastectomy (BRRM) with and without different types of reconstruction, risk-reducing salpingo-oophorectomy (RRSO), and their combinations with corresponding reimbursements in the statutory health-care system in Germany. PATIENTS AND METHODS: Real total costs of care for BRRM with and without reconstruction, RRSO, and their combinations were calculated as the sum of all personnel and technical costs. These costs calculated in a German University hospital were compared with the sum of all reimbursements in the German DRG-based health-care system. RESULTS: While sole RRSO, BRRM without reconstruction, and BRRM with secondary DIEP (deep inferior epigastric perforator)-reconstruction still result in a small benefit, we even found shortfalls for the hospital with all other prophylactic operations under consideration. The calculated deficits were especially high for BRRM with implant-based breast reconstruction and for combined operations when the risk reduction is achieved with a minimum of separate operations. CONCLUSIONS: Risk-reducing surgery in BRCA-mutation carriers is frequently not cost-covering for the executing hospitals in the German health-care system. Thus, appropriate concepts are required to ensure a nationwide care.
CRIS-Team Scopus Importer:2019-09-24
Keywords: BRCA; Breast cancer; Cost effectiveness; Genetic counseling; Ovarian cancer